Voluntary and Involuntary Constraints on the Conduct of Macroeconomic Policy: An Application to the UK. Issue 1 (2nd January 2021) - Pantelopoulos, George; Watts, Martin
Abstract: Modern Monetary Theory advocates make the distinction between voluntary and involuntary constraints with respect to operation of key institutions, such as the Central Bank and Treasury, in their conduct of macroeconomic policy. In this article we explore several episodes of UK policymaking, in order to demonstrate consistency regarding the policy coordination between HM Treasury and the Bank of England, and, in addition, highlight numerous voluntary constraints which by their very nature can be finessed when circumstances demand. In particular, we show that the use of the Ways and Means account on a number of notable occasions has meant that Government spending was not constrained by prospective tax receipts and sales of Government securities. Also, the introduction of non-convertible banknotes and other strategies, including the financing of the First War Loan, meant that the prevailing voluntary constraints were sidestepped.